THE CURRENT STATE OF THE LEGISLATIVE ENSURANCE OF THE MARKET REGULATION OF CRYPTO CURRENCY IN UKRAINE - Ustynova, Iryna P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: conduct a review of the current state of regulation of the crypto market in Ukraine and express their views on the legal regulation of this institution in Ukraine. Methods of research: within the framework of European integration directions of development of Ukraine and improvement of development of the level of protection of the rights of persons, ways of improvement of economy, globalization, spread of IT technologies more and more. This directly influences the emergence of new financial institutions, tools and forms of interaction between people. With this rapid development, an analogue of traditional currencies, cryptocurrency, has emerged. Thus there is a need to study the features and trends of cryptocurrency development and regulation of the development of this system. Results: over the last 5 years, research on the crypto market has been conducted quite actively by economists. As for the lawyers of researchers, such scientists as Derevyanko B., Ustimenko V., Pashchenko K., Golubeva N., Grebenyuk M., Vorontsova S., Doronin I., Kovalchuk A., Stetsenko S., Solovyova A. have made a significant contribution to legal science in these matters. Discussion: today, as in many countries, the legal status of cryptocurrency is absent. At the same time, there is a «bold» introduction of the instruments of this market into the economy of Ukraine. Imperfect regulation and research on this crypto issue somewhat hinders the development of this sector and technology.